Performance of Pharmacy students in a comprehensive medication management service in a Primary Health Care Setting (Research, Society and Development, 2021)
This study aims to assess the performance of pharmacy students in the provision of a comprehensive medication management (CMM) service in a primary health care setting. Methods: A retrospective, descriptive, observational study spanning one academic semester of the provision of the CMM service by pharmacy students was conducted. The data on the profile of patients attended, drug therapy-related problems (DRPs) identified, and the interventions proposed to resolve the DRPs were collected from electronic medical records held by the service. Key findings: A total of 20 patients were attended, predominantly women (65%), with a mean age of 69.2 years. The mean number of health problems per patient was 4.8 and mean medications per patient was 6.8. Of the total 35 DRPs identified, the most common were those related to indication (40%) and effectiveness (22.9%) of the drug therapy. The two most frequent interventions to resolve the DRPs involved starting new therapy and changing dosage, respectively. Conclusions: The results allowed inferences to be made about the effectiveness of pharmacy practice experience for developing clinical competencies of pharmacy students, given that the performance of students proved comparable to that of pharmacists in established CMM services reported in the literature.